An all-solid-state sulfide electrolyte membrane, a preparation method therefor, and use thereof
Patent Information
- Application Number
- CN202611088957.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-22
AI Technical Summary
本发明所述硫化物固态电解质膜及其制备方法中,针对现有硫化物固态电解质膜的缺陷,通过粒径级配、正负极界面优化、粘结剂体系优化,实现了硫化物固态电解质膜综合性能的全面突破;具体地,本发明采用大小不同粒径的硫化物电解质(如Li6PS5Cl)颗粒级配方式,实现紧密堆积,提高体相离子电导率与致密度,有效抑制锂枝晶生长;通过将锂盐如二氟磷酸锂(LiDFP)均匀分散于电解质浆料中,利用其在充放电过程中优先分解的特性,在正极侧原位生成富LiF的稳定CEI层,抑制高电压下界面副反应与阻抗上升;采用ENBR作为粘结剂,在较低添加量下即可实现优秀的粘结性,确保膜层结构完整、机械强度好、不掉粉。
Smart Images

Figure CN122599510B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of all-solid-state battery technology, specifically to an all-solid-state sulfide electrolyte membrane, its preparation method, and its application. Background Technology
[0002] Sulfide electrolytes (such as sulfide-germanium ore type Li6PS5Cl) are characterized by extremely high ionic conductivity (up to 10 at room temperature). -3 With advantages such as low density (on the order of S / cm), cold pressing, low interfacial impedance, and good mechanical flexibility, it is considered a core electrolyte material for all-solid-state lithium batteries. However, conventional single-particle-size, uncoated sulfide electrolyte films currently suffer from problems such as poor interfacial compatibility, difficulty in balancing density and ionic conductivity, and limited mechanical strength and resistance to lithium dendrite formation. Furthermore, they cannot effectively suppress interfacial issues with the positive and negative electrodes: the positive electrode side is prone to oxidation and decomposition under high voltage, resulting in a rapid increase in interfacial impedance; while the negative electrode side suffers from lithium dendrite growth.
[0003] Regarding cathode interface modification, the poor interfacial compatibility between sulfide electrolytes and high-voltage oxide cathodes is a core bottleneck restricting the performance improvement of all-solid-state lithium batteries. Under high-voltage operating conditions, sulfide electrolytes are prone to oxidative decomposition on the cathode side, leading to a continuous surge in interfacial impedance and rapid degradation of battery cycle life.
[0004] Chinese patent document CN121260889A discloses a sulfide solid electrolyte membrane, its preparation method, and an all-solid-state lithium battery. This solid electrolyte membrane consists only of a sulfide solid electrolyte and a binder, without any liquid components. A non-polar anti-solvent thickening technique is used to prepare a uniformly dispersed electrolyte slurry with excellent stability, thereby producing a sulfide solid electrolyte membrane of uniform thickness. Specifically, the binder is dissolved in an organic solvent with excellent stability to the sulfide electrolyte, and then the solid electrolyte powder is added to the solvent. After coating and drying, the sulfide solid electrolyte membrane is obtained. This method can achieve large-scale preparation of sulfide solid electrolyte membranes without changing existing lithium-ion battery membrane fabrication processes. Furthermore, this electrolyte membrane has high ionic conductivity and flexibility, which is beneficial for stable battery cycling. However, this patent lacks lithium salt interface modification and particle size distribution design, making the binder prone to agglomeration during mixing, resulting in insufficient interface stability, membrane density, and ion transport performance.
[0005] In summary, it is of great importance to provide a sulfide solid electrolyte membrane, its preparation method, and its application to solve the above problems. Summary of the Invention
[0006] The technical problem to be solved by this invention is that existing sulfide electrolytes suffer from poor interface compatibility with high-voltage cathodes, high interface impedance, insufficient film density, and poor cycle stability. This invention provides an all-solid-state sulfide electrolyte membrane, its preparation method, and its application. The sulfide electrolyte membrane is prepared by binary particle size distribution design of electrolyte particles, synergistic modification of lithium salt (LiDFP) and epoxy-modified nitrile rubber ENBR, and homogeneous dispersion in a dual-solvent system.
[0007] To solve the above-mentioned technical problems, the first aspect of the present invention provides an all-solid-state sulfide electrolyte membrane, comprising lithium salt, binder, and sulfide electrolyte particles; The adhesive is epoxy-modified nitrile rubber (ENBR). The sulfide electrolyte particles include a first sulfide electrolyte particle and a second sulfide electrolyte particle, wherein the first sulfide electrolyte particle has a D50 of 3μm to 10μm, preferably 4μm to 8μm, and a SPAN value ≤ 2.0, preferably 1.0-2.0; the second sulfide electrolyte particle has a D50 of 0.1μm to 2.5μm, preferably 0.5μm to 2μm, and a SPAN value ≤ 2.0, preferably 1.0-2.0.
[0008] In this invention, the binder contains epoxy groups, which can uniformly disperse lithium salt.
[0009] According to some embodiments of the present invention, based on the mass of the all-solid sulfide electrolyte membrane as 100%, the mass content of the lithium salt is 0.5% to 2.0%; the mass content of the binder is 1.5% to 2.0%; the mass content of the first sulfide electrolyte particles is 76% to 89%; and the mass content of the second sulfide electrolyte particles is 9% to 20%.
[0010] According to some embodiments of the present invention, the mass ratio of the first sulfide electrolyte particle to the second sulfide electrolyte particle is (4-10):1, preferably (5-9):1.
[0011] According to some embodiments of the present invention, the first sulfide electrolyte particle and the second sulfide electrolyte particle may be made of the same or different materials, and each is independently selected from lithium-based inorganic sulfide electrolytes, such as Li6PS5Cl, Li6PS5Br, Li6PS5I, Li 5.5 PS 4.5 Cl 1.5 At least one of the following, preferably Li6PS5Cl.
[0012] According to some embodiments of the present invention, the lithium salt is selected from at least one of lithium difluorophosphate (LiDFP), lithium bisfluorosulfonylimide (LiFSI), lithium difluorooxalate borate (LiDFOB), lithium tetrafluoroborate (LiBF4), and lithium bistrifluoromethylsulfonylimide (LiTFSI), preferably lithium difluorophosphate (LiDFP) and / or lithium bisfluorosulfonylimide (LiFSI), and more preferably lithium difluorophosphate (LiDFP).
[0013] In this invention, there are no special requirements for the preparation method of the epoxy-modified nitrile butadiene rubber (NBR), all of which are conventional techniques in the art. For example, in some embodiments of this invention, the preparation method of the epoxy-modified NBR includes: mixing 8g-12g of NBR with 120mL-150mL of a non-polar solvent (xylene) until completely dissolved; heating the system to 60℃-70℃; adding 8.0g-10.0g of glacial acetic acid (purity ≥99%) to the mixed solution; and then slowly adding 15.0g-20g dropwise. A 30wt% hydrogen peroxide aqueous solution was prepared and reacted at a constant temperature for 4-6 hours. After the reaction was completed, the reaction mixture was neutralized with a 3wt%-5wt% sodium carbonate solution to adjust the pH to 7-7.5. The neutralized reaction mixture was then coagulated in anhydrous ethanol to precipitate polymer solids, which were washed 2-4 times. The obtained polymer solids were placed in a vacuum oven and dried at 60-70℃ for 24-48 hours until constant weight was achieved, completely removing residual solvents and moisture, thus obtaining epoxy-modified nitrile butadiene rubber (ENBR).
[0014] In this invention, the lithium salt, such as lithium difluorophosphate (LiDFP), has a wide electrochemical stability window and excellent lithium-ion conductivity. During charging and discharging, it can preferentially undergo electrochemical decomposition compared to sulfide electrolytes, generating LiF in situ at the interface. This constructs a LiF-rich positive electrode electrolyte interface layer (CEI) on the positive electrode side, suppressing the oxidative decomposition of sulfides under high voltage and significantly improving the interface ion conduction efficiency and battery cycle stability.
[0015] In this invention, since large-diameter electrolyte particles have fewer grain boundaries and higher bulk ionic conductivity, small-diameter electrolyte particles can fill the gaps between large-diameter electrolyte particles, improve the film density, suppress lithium dendrite growth on the negative electrode side, and improve cycle life. Therefore, by mixing two different sizes of sulfide electrolyte particles in a specific mass ratio, the density, ionic conductivity, and mechanical properties of the sulfide electrolyte film can be effectively improved.
[0016] In this invention, the epoxy-modified nitrile rubber (ENBR) binder can form a uniform and continuous highly elastic polar phase on the surface of electrolyte particles, effectively improving the mechanical strength of the electrolyte membrane. Simultaneously, the epoxy groups on the ENBR molecular chain can undergo a controlled ring-opening reaction with lithium salts such as lithium difluorophosphate (LiDFP), anchoring the lithium salts (LiDFP) to the polymer chain through chemical bonding. This achieves uniform dispersion in the slurry, forming a polymer-lithium salt uniformly dispersed composite structure where the ENBR molecular chain is anchored to LiDFP via epoxy ring-opening covalent bonding. During charge and discharge, this structure facilitates the in-situ formation of a uniform and dense LiF-rich positive electrode electrolyte interface (CEI) layer, effectively inhibiting the oxidative decomposition of sulfide electrolyte particles. Furthermore, the epoxy-modified ENBR binder can react with free Li on the surface of sulfide electrolyte particles (LPSC). + Strong interactions are formed, creating a stable, elastic network between particles. This network not only ensures continuous lithium-ion conduction but also effectively buffers volume changes during charging and discharging, significantly improving the mechanical strength and structural integrity of the electrolyte membrane.
[0017] A second aspect of the present invention provides a method for preparing the all-solid-state sulfide electrolyte membrane provided in the first aspect above, the method comprising: (1) The binder and non-polar solvent are first mixed to obtain mixture a; (2) Mix the mixture a obtained in step (1) with a polar solvent and a lithium salt to obtain mixture b; (3) The sulfide electrolyte particles and the mixture b obtained in step (2) are mixed for a third time to obtain an electrolyte slurry; (4) The electrolyte slurry obtained in step (3) is coated on the substrate to obtain a wet film. The wet film is then vacuum dried to obtain the all-solid sulfide electrolyte membrane.
[0018] According to some embodiments of the present invention, in step (1), the non-polar solvent is p-xylene, which affects the chemical stability of the sulfide electrolyte of the sulfide type.
[0019] According to some embodiments of the present invention, in step (1), the conditions for the first mixing include: a temperature of 20°C to 30°C and a time of 24h to 48h.
[0020] According to some embodiments of the present invention, in step (2), the polar solvent is selected from at least one of acetonitrile, ethyl acetate, and dimethyl carbonate.
[0021] According to some embodiments of the present invention, in step (2), the conditions for the second mixing include: a temperature of 20°C to 30°C and a time of 12h to 24h.
[0022] According to some embodiments of the present invention, in step (3), the conditions for the third mixing include: a temperature of 20°C to 30°C, a time of 30 min to 40 min, and a stirring rate of 200 rpm to 300 rpm.
[0023] In this invention, the first sulfide electrolyte particles and the second sulfide electrolyte particles are manually turned and premixed in a homogenizing bottle according to a mass ratio to obtain the sulfide electrolyte particles, which are then mixed with mixture b for a third time.
[0024] According to some embodiments of the present invention, in step (4), the thickness of the wet film is 40 μm to 60 μm.
[0025] In this invention, there are no particular limitations on the selection of the substrate, and all are conventional technical means in the art. For example, in some embodiments, the substrate is selected from aluminum foil.
[0026] In this invention, there is no particular limitation on the coating method, all of which are conventional technical means in the field. For example, in some embodiments, the coating method is to use a doctor blade for coating.
[0027] According to some embodiments of the present invention, in step (4), the conditions for vacuum drying include: a temperature of 80°C to 100°C and a time of 12h to 24h.
[0028] In this invention, the vacuum drying is carried out in a vacuum drying oven; and the preparation method further includes, after vacuum drying, removing the electrolyte membrane along with the substrate from the vacuum drying oven, cooling it to room temperature, and then peeling off the substrate to obtain the all-solid-state sulfide electrolyte membrane.
[0029] According to some embodiments of the present invention, in the preparation method, the mass ratio of nonpolar solvent to polar solvent is (2-9):1, preferably (4-7):1; and / or, the mass ratio of binder to lithium salt is (0.5-5):1, preferably (1-3):1; and / or, in the electrolyte slurry, the mass ratio of binder, sulfide electrolyte particles and lithium salt is 1:(40-70):(0.1-1), preferably 48, 64.7, 65.3; 0.3, 1; and / or, in the electrolyte slurry, the total mass content of binder, sulfide electrolyte particles and lithium salt is 40% to 60%.
[0030] In this invention, the preparation method is carried out in an argon atmosphere in a glove box, and the water and oxygen content is ≤0.1ppm; in this invention, the water content of the non-polar solvent and the polar solvent should be <10ppm.
[0031] In this invention, the all-solid-state sulfide electrolyte membrane is prepared by uniformly dispersing lithium salts such as lithium difluorophosphate (LiDFP) and binder epoxy-modified nitrile rubber (ENBR) in a dual-solvent system, and using sulfide electrolyte particles (LPSC) of different sizes for gradation to achieve interface control and bulk optimization of the electrolyte layer: Utilizing the characteristic that lithium salts such as lithium difluorophosphate (LiDFP) preferentially decompose in situ to generate LiF during charging and discharging, a LiF-rich interface layer is constructed on the positive electrode side, effectively suppressing the oxidative decomposition of the sulfide electrolyte under high voltage; the particle size gradation of the sulfide electrolyte particles improves the density and mechanical strength of the electrolyte membrane, eliminates internal porosity, inhibits lithium dendrite penetration, and achieves long-term stability of the negative electrode interface; simultaneously, the continuous high-polarity elastic phase formed in the electrolyte membrane by the binder epoxy-modified nitrile rubber (ENBR) and its interaction with Li... + The strong interaction between the sulfide electrolyte particles creates a stable interfacial bonding network, which not only ensures the lithium-ion transport path but also buffers the volume changes during charging and discharging.
[0032] A third aspect of the present invention provides an all-solid-state battery, comprising the all-solid-state sulfide electrolyte membrane provided in the first aspect or the all-solid-state sulfide electrolyte membrane prepared by the preparation method provided in the second aspect.
[0033] Beneficial effects: The sulfide solid electrolyte membrane and its preparation method described in this invention address the shortcomings of existing sulfide solid electrolyte membranes by optimizing particle size distribution, the positive and negative electrode interfaces, and the binder system, achieving a comprehensive breakthrough in the overall performance of the sulfide solid electrolyte membrane. Specifically, this invention employs a particle size distribution method for sulfide electrolytes (such as Li6PS5Cl) of different sizes to achieve close packing, improve bulk ionic conductivity and density, and effectively suppress lithium dendrite growth. By uniformly dispersing lithium salts such as lithium difluorophosphate (LiDFP) in the electrolyte slurry, and utilizing its preferential decomposition during charging and discharging, a stable LiF-rich CEI layer is generated in situ on the positive electrode side, suppressing interfacial side reactions and impedance rise under high voltage. Using ENBR as a binder, excellent adhesion can be achieved at a low addition amount, ensuring the integrity of the membrane structure, good mechanical strength, and no powder shedding. Attached Figure Description
[0034] Figure 1 This is the XRD pattern of the electrolyte membrane prepared in Example 1 of the present invention. Detailed Implementation
[0035] The present invention will be further described below with reference to embodiments. However, the present invention is not limited to these embodiments.
[0036] Unless otherwise specified, all raw materials used in the following embodiments and comparative examples of the present invention are commercially available.
[0037] Unless otherwise specified, the ambient temperature / room temperature conditions described in the embodiments and comparative examples of this invention are all 25°C.
[0038] In the embodiments and comparative examples of this invention, the preparation methods were all carried out in an argon atmosphere in a glove box, and the water and oxygen content was ≤0.1ppm. In the embodiments and comparative examples of this invention, the water content of the non-polar solvent and the polar solvent was <10ppm.
[0039] In the embodiments and comparative examples of this invention, during XRD testing, a sulfide all-solid electrolyte membrane was wrapped with a polyimide film (100 μm) to isolate it from air. Cu target Kα radiation (λ=1.5406 Å) was used, with an operating voltage of 40 kV, an operating current of 40 mA, a 2θ scan range of 10° to 80°, a step size of 0.01°, and a scan speed of 2° / min.
[0040] Example 1 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. (1) 10g of nitrile butadiene rubber (NBR) (acrylonitrile content 25wt.%) was placed in a 500mL round-bottom flask, and 133.75mL of xylene solvent was added. The mixture was stirred with a magnetic stirrer until completely dissolved. The system was heated to 65℃, and 9.0g of glacial acetic acid (purity ≥99%) was added to the mixture. Then, 17.0g of 30wt% hydrogen peroxide aqueous solution was slowly added dropwise. The mixture was reacted at 65℃ for 6h. After the reaction was completed, the reaction mixture was neutralized with 5wt% sodium carbonate solution to adjust the pH to 7.0. The neutralized reaction mixture was then coagulated in anhydrous ethanol to precipitate the polymer and washed 3 times. The resulting solid was placed in a vacuum oven and dried under vacuum at 70℃ for 48h to constant weight to completely remove residual solvent and water, thus obtaining epoxy-modified nitrile butadiene rubber (ENBR). The ENBR contained approximately 25 wt.% nitrile groups and approximately 3.6 mol% epoxy groups (relative to butadiene units).
[0041] (2) Weigh 0.075g of epoxy-modified nitrile rubber (ENBR), add it to 4.25g of p-xylene, seal it and stir at room temperature for 48h until the epoxy-modified nitrile rubber (ENBR) is completely dissolved to obtain a homogeneous and transparent mixture a; (3) Add 0.75g acetonitrile and 0.075g lithium difluorophosphate (LiDFP) to mixture a, stir at room temperature for 24h until lithium difluorophosphate (LiDFP) is completely dispersed without agglomeration, to obtain mixture b; (4) Weigh 4.365g of large-particle-size (D50=6μm, SPAN=1) Li6PS5Cl and 0.485g of small-particle-size (D50=1μm, SPAN=1) Li6PS5Cl, place them in a homogenizing bottle and manually turn them over to premix evenly to obtain graded mixed electrolyte powder. (5) Add all of the mixture b to the above mixed electrolyte powder at once, seal the homogenizing bottle, and stir at 300 rpm for 40 min at room temperature to obtain an electrolyte slurry with a total mass of 10 g and a solid content of 50%. (6) The electrolyte slurry is evenly coated on the smooth aluminum foil substrate by a scraper, and the wet film thickness is controlled to be 40 μm. Then it is transferred to a vacuum drying oven and vacuum dried at 80°C for 24 h. After cooling to room temperature, the substrate is peeled off and cut into round pieces with a diameter of 10 mm to obtain a sulfide all-solid electrolyte membrane.
[0042] The XRD test results of the sulfide all-solid-state electrolyte membrane prepared in Example 1 are shown in the figure. Figure 1 .
[0043] The charge-discharge performance of the sulfide all-solid-state electrolyte membrane prepared in Example 1 was tested: 0.5g of lithium nickel cobalt manganese oxide (LiNi) was taken. 0.8 Co 0.1 Mn 0.1 The positive electrode material (NCM811) was ground and mixed under an argon atmosphere for 30 minutes according to the mass ratio of NCM811:Li6PS5Cl:VGCF = 80:19:1 to obtain the positive electrode material. 10 mg of the above positive electrode material was used as the positive electrode, the sulfide all-solid electrolyte membrane prepared in Example 1 was used as the intermediate electrolyte layer, and the lithium indium alloy was used as the negative electrode to assemble an all-solid mold battery. The battery was pressurized to 180 MPa through an external clamp and allowed to stand for 10 hours. The battery was activated by charging and discharging at a rate of 0.1C for one cycle within a voltage range of 2.1-3.7V. A constant current charge-discharge cycle test was then performed at a rate of 0.5C to obtain the specific capacity of the first charge cycle, the specific capacity of the first discharge cycle, the efficiency of the first charge-discharge cycle, and the cycle capacity retention rate. The results are shown in Table 1.
[0044] Ionic conductivity test: Three sulfide all-solid electrolyte membranes prepared in Example 1 above were stacked in the PEEK tube of the mold battery. A smooth aluminum foil was placed on the top and bottom of the sulfide all-solid electrolyte membrane as a blocking electrode. The membrane was pressed with a pressure of 300 MPa for 2 min. The room temperature ionic conductivity of the sulfide all-solid electrolyte membrane was tested by AC impedance method. The results are shown in Table 2.
[0045] Example 2 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. (1) 10g of nitrile butadiene rubber (NBR) (acrylonitrile content 25wt.%) was placed in a 500mL round-bottom flask, and 133.75mL of xylene solvent was added. The mixture was stirred with a magnetic stirrer until completely dissolved. The system was heated to 65℃, and 9.0g of glacial acetic acid (purity ≥99%) was added to the mixture. Then, 17.0g of 30wt% hydrogen peroxide aqueous solution was slowly added dropwise. The mixture was reacted at 65℃ for 6h. After the reaction was completed, the reaction mixture was neutralized with 5wt% sodium carbonate solution to adjust the pH to 7.0. The neutralized reaction mixture was then coagulated in anhydrous ethanol to precipitate the polymer and washed 3 times. The resulting solid was placed in a vacuum oven and dried under vacuum at 70℃ for 48h to constant weight to completely remove residual solvent and water, thus obtaining epoxy-modified nitrile butadiene rubber (ENBR). The ENBR contained approximately 25 wt.% nitrile groups and approximately 3.6 mol% epoxy groups (relative to butadiene units).
[0046] (2) Weigh 0.06g of epoxy-modified nitrile rubber (ENBR), add it to 4.8g of p-xylene, seal it and stir at room temperature for 48h until the epoxy-modified nitrile rubber (ENBR) is completely dissolved to obtain a homogeneous and transparent mixture a; (3) Add 1.2g acetonitrile and 0.02g lithium difluorophosphate (LiDFP) to mixture a, stir at room temperature for 24h until the lithium difluorophosphate (LiDFP) is completely dispersed without agglomeration, to obtain mixture b; (4) Weigh 3.528g of large-particle-size (D50=6μm, SPAN=1) Li6PS5Cl and 0.392g of small-particle-size (D50=1μm, SPAN=1) Li6PS5Cl, place them in a homogenizing bottle and manually turn them over to premix evenly to obtain graded mixed electrolyte powder. (5) Add all of the mixture b to the above mixed electrolyte powder at once, seal the homogenizing bottle, and stir at 300 rpm for 40 min at room temperature to obtain an electrolyte slurry with a total mass of 10 g and a solid content of 40%. (6) The electrolyte slurry is evenly coated on the smooth aluminum foil substrate by a scraper, and the wet film thickness is controlled to be 40 μm. Then it is transferred to a vacuum drying oven and vacuum dried at 80°C for 24 h. After cooling to room temperature, the substrate is peeled off and cut into round pieces with a diameter of 10 mm to obtain a sulfide all-solid electrolyte membrane.
[0047] The charge-discharge performance of the sulfide all-solid-state electrolyte membrane prepared in Example 2 was tested: 0.5g of lithium nickel cobalt manganese oxide (LiNi) was taken. 0.8 Co 0.1 Mn 0.1The positive electrode material (NCM811) was ground and mixed under an argon atmosphere for 30 min at a mass ratio of NCM811:Li6PS5Cl:VGCF = 80:19:1 to obtain the positive electrode material. 10 mg of the above positive electrode material was used as the positive electrode, the sulfide all-solid-state electrolyte membrane prepared in Example 2 was used as the intermediate electrolyte layer, and the lithium-indium alloy was used as the negative electrode to assemble an all-solid-state mold battery. The battery was pressurized to 180 MPa using an external clamp and allowed to stand for 10 h. Then, the battery was activated by charging and discharging at a rate of 0.1C within a voltage range of 2.1-3.7V. A constant current charge-discharge cycle test was then performed at a rate of 0.5C to obtain the specific capacity of the first charge cycle, the specific capacity of the first discharge cycle, the efficiency of the first charge-discharge cycle, and the cycle capacity retention rate. The results are shown in Table 1.
[0048] Ionic conductivity test: Three sulfide all-solid electrolyte membranes prepared in Example 1 above were stacked in the PEEK tube of the mold battery. A smooth aluminum foil was placed on the top and bottom of the sulfide all-solid electrolyte membrane as a blocking electrode. The membrane was pressed at 300 MPa for 2 min. The room temperature ionic conductivity of the electrolyte membrane was tested by AC impedance method. The results are shown in Table 2.
[0049] Example 3 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. (1) 10g of nitrile butadiene rubber (NBR) (acrylonitrile content 25wt.%) was placed in a 500mL round-bottom flask, and 133.75mL of xylene solvent was added. The mixture was stirred with a magnetic stirrer until completely dissolved. The system was heated to 65℃, and 9.0g of glacial acetic acid (purity ≥99%) was added to the mixture. Then, 17.0g of 30wt% hydrogen peroxide aqueous solution was slowly added dropwise. The mixture was reacted at 65℃ for 6h. After the reaction was completed, the reaction mixture was neutralized with 5wt% sodium carbonate solution to adjust the pH to 7.0. The neutralized reaction mixture was then coagulated in anhydrous ethanol to precipitate the polymer and washed 3 times. The resulting solid was placed in a vacuum oven and dried under vacuum at 70℃ for 48h to constant weight to completely remove residual solvent and water, thus obtaining epoxy-modified nitrile butadiene rubber (ENBR). The ENBR contained approximately 25 wt.% nitrile groups and approximately 3.6 mol% epoxy groups (relative to butadiene units).
[0050] (2) Weigh 0.12g of epoxy-modified nitrile rubber (ENBR), add it to 3.6g of p-xylene, seal it and stir at room temperature for 48h until the epoxy-modified nitrile rubber (ENBR) is completely dissolved to obtain a homogeneous and transparent mixture a; (3) Add 0.4 g acetonitrile and 0.12 g lithium difluorophosphate (LiDFP) to mixture a, stir at room temperature for 24 h until lithium difluorophosphate (LiDFP) is completely dispersed without agglomeration, to obtain mixture b; (4) Weigh 5.184g of large-particle-size (D50=6μm, SPAN=1) Li6PS5Cl and 0.576g of small-particle-size (D50=1μm, SPAN=1) Li6PS5Cl, place them in a homogenizing bottle and manually turn them over to premix evenly to obtain graded mixed electrolyte powder. (5) Add all of the mixture b to the above mixed electrolyte powder at once, seal the homogenizing bottle, and stir at 300 rpm for 40 min at room temperature to obtain an electrolyte slurry with a total mass of 10 g and a solid content of 60%. (6) The electrolyte slurry is evenly coated on the smooth aluminum foil substrate by a scraper, and the wet film thickness is controlled to be 40 μm. Then it is transferred to a vacuum drying oven and vacuum dried at 80°C for 24 h. After cooling to room temperature, the substrate is peeled off and cut into round pieces with a diameter of 10 mm to obtain a sulfide all-solid electrolyte membrane.
[0051] The charge-discharge performance of the sulfide all-solid-state electrolyte membrane prepared in Example 3 was tested: 0.5g of lithium nickel cobalt manganese oxide (LiNi) was taken. 0.8 Co 0.1 Mn 0.1 The positive electrode material (NCM811) was ground and mixed in an argon atmosphere for 30 min at a mass ratio of NCM811:Li6PS5Cl:VGCF = 80:19:1 to obtain the positive electrode material. 10 mg of the above positive electrode material was used as the positive electrode, the sulfide all-solid-state electrolyte membrane prepared in Example 3 was used as the intermediate electrolyte layer, and the lithium-indium alloy was used as the negative electrode to assemble an all-solid-state mold battery. The battery was pressurized to 180 MPa using an external clamp and allowed to stand for 10 h. Then, the battery was activated by charging and discharging at a rate of 0.1C within a voltage range of 2.1-3.7V. A constant current charge-discharge cycle test was then performed at a rate of 0.5C to obtain the specific capacity of the first charge cycle, the specific capacity of the first discharge cycle, the efficiency of the first charge-discharge cycle, and the cycle capacity retention rate. The results are shown in Table 1.
[0052] Ionic conductivity test: Three sulfide all-solid electrolyte membranes prepared in Example 3 above were stacked in the PEEK tube of the mold battery. A smooth aluminum foil was placed on the top and bottom of the sulfide all-solid electrolyte membrane as a blocking electrode. The membrane was pressed with a pressure of 300 MPa for 2 min. The room temperature ionic conductivity of the electrolyte membrane was tested by AC impedance method. The results are shown in Table 2.
[0053] Example 4 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that in step (4), the large-particle-size Li6PS5Cl has a D50 of 8 μm and a SPAN of 1.
[0054] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0055] Example 5 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that in step (4), the large-particle-size Li6PS5Cl has a D50 of 4 μm and a SPAN of 1.
[0056] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0057] Example 6 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that in step (4), the small-particle-size Li6PS5Cl has a D50 of 2 μm and a SPAN of 1.
[0058] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0059] Example 7 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that in step (4), the small-particle-size Li6PS5Cl has a D50 of 0.5 μm and a SPAN of 1.
[0060] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0061] Example 8 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that lithium difluorophosphate (LiDFP) is replaced with lithium bisfluorosulfonylimide (LiFSI) of equal mass.
[0062] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0063] Example 9 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that in step (4), 4.244g of large-particle-size (D50=6μm, SPAN=1) Li6PS5Cl and 0.606g of small-particle-size (D50=1μm, SPAN=1) Li6PS5Cl are weighed, and the mass ratio of the two is 7:1.
[0064] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0065] Example 10 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that in step (4), 4.042g of large-particle-size (D50=6μm, SPAN=1) Li6PS5Cl and 0.808g of small-particle-size (D50=1μm, SPAN=1) Li6PS5Cl are weighed, and the mass ratio of the two is 5:1.
[0066] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0067] Example 11 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that in step (2), the amount of p-xylene fed is 4.375g; in step (3), the amount of acetonitrile fed is 0.625g, and the mass ratio of non-polar solvent to polar solvent is 7:1.
[0068] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0069] Example 12 This embodiment is used to illustrate the all-solid-state sulfide electrolyte membrane and its preparation method described in this invention. The preparation method is the same as in Example 1, except that in step (2), 0.1125g of epoxy-modified nitrile rubber (ENBR) is weighed, and in step (3), 0.0375g of lithium difluorophosphate (LiDFP) is added. The mass ratio of epoxy-modified nitrile rubber to lithium salt is 3:1.
[0070] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0071] Comparative Example 1 The preparation method is the same as in Example 1, except that lithium difluorophosphate is not added, and the solid content of the final electrolyte slurry is 49.62%.
[0072] The charge-discharge performance test results of the obtained sulfide all-solid-state electrolyte membrane are shown in Table 1 and 2. Figure 1 The results of the ionic conductivity test are shown in Table 2.
[0073] Comparative Example 2 The preparation method is the same as in Example 1, except that: in step (2), 0.5g of epoxy-modified nitrile rubber (ENBR) is weighed and 4.675g of p-xylene is added; the content of epoxy-modified nitrile rubber (ENBR) in the obtained electrolyte slurry is increased to 5%, and the solid content of the final electrolyte slurry is 50%.
[0074] The charge-discharge performance test results of the obtained sulfide all-solid-state electrolyte membrane are shown in Table 1 and 2. Figure 1 The results of the ionic conductivity test are shown in Table 2.
[0075] Comparative Example 3 The preparation method is the same as in Example 1, except that the mixed electrolyte powder consists only of 4.85g of large-particle-size (D50=6μm, SPAN=1) Li6PS5Cl.
[0076] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0077] Comparative Example 4 The preparation method is the same as in Example 1, except that the mixed electrolyte powder consists of only 4.85g of Li6PS5Cl with a small particle size (D50=1μm, SPAN=1).
[0078] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0079] Comparative Example 5 The preparation method is the same as in Example 1, except that an equal mass of polyvinylidene fluoride homopolymer (PVDF, McLean, grade P650822) is used instead of epoxy-modified nitrile butadiene rubber (ENBR).
[0080] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0081] Comparative Example 6 The preparation method is the same as in Example 1, except that an equal mass of nitrile rubber (acrylonitrile content 25 wt.%) is used to replace epoxy modified nitrile rubber (ENBR).
[0082] The charge-discharge performance test results of the obtained sulfide all-solid electrolyte membrane are shown in Table 1; the ionic conductivity test results are shown in Table 2.
[0083] Table 1 First Cycle Charge / Discharge Data
[0084] Table 2 Ionic conductivity test data
[0085] In Table 2, thickness, area, and impedance are only used as part of the calculation process in the test method of ionic conductivity, and have no impact on the performance and test conclusions of the sulfide all-solid electrolyte membrane described in this invention.
[0086] As can be seen from Tables 1-2, the all-solid-state sulfide electrolyte membranes prepared in Examples 1-12 of this invention exhibit high first-cycle charge capacity and first-cycle discharge capacity during charge-discharge performance testing. They also demonstrate high first-cycle charge-discharge efficiency and high cycle capacity retention, particularly Example 1, which boasts a cycle capacity retention of 85.31%. Furthermore, the all-solid-state sulfide electrolyte membranes prepared in Examples 1-12 exhibit high room-temperature ionic conductivity (≥1.46 mS / cm). In contrast, Comparative Example 1, unlike Example 1, did not contain lithium difluorophosphate, although... The changes in the first-cycle charging capacity and first-cycle discharging capacity were not significant, but the first-cycle charge / discharge efficiency, cycle capacity retention, and room-temperature ionic conductivity decreased significantly. In Comparative Example 2, compared to Example 1, the content of epoxy-modified nitrile rubber was increased, resulting in a significant decrease in the first-cycle charging capacity and first-cycle discharging capacity, as well as a significant decrease in the first-cycle charge / discharge efficiency, cycle capacity retention, and room-temperature ionic conductivity. In Comparative Example 3, compared to Example 1, only large-particle-size electrolyte powder was used, resulting in significant changes in the first-cycle charging capacity, first-cycle discharging capacity, first-cycle charge / discharge efficiency, cycle capacity retention, and room-temperature ionic conductivity. The ionic conductivity of all samples decreased significantly. In Comparative Example 4, compared to Example 1, only small-particle-size electrolyte powder was used, resulting in a significant decrease in the first-cycle charge capacity, first-cycle discharge capacity, first-cycle charge / discharge efficiency, cycle capacity retention, and room-temperature ionic conductivity. In Comparative Example 5, compared to Example 1, a conventional binder, polyvinylidene fluoride homopolymer, was used to replace the ENBR of this invention, resulting in a significant decrease in the first-cycle charge capacity, first-cycle discharge capacity, first-cycle charge / discharge efficiency, cycle capacity retention, and room-temperature ionic conductivity. In Comparative Example 6, compared to Example 1, unmodified nitrile rubber was used to replace... The ENBR of this invention significantly reduces the specific capacity of the first charge cycle, the specific capacity of the first discharge cycle, the first charge / discharge efficiency, the cycle capacity retention rate, and the room temperature ionic conductivity. This demonstrates that the selection of the binder (epoxy-modified nitrile rubber), the particle size distribution of the sulfide electrolyte (such as Li6PS5Cl), and the addition of lithium salt can solve the problems of poor interface compatibility, high interface impedance, insufficient film density, and poor cycle stability of existing sulfide electrolytes with high-voltage cathodes, achieving a comprehensive breakthrough in the overall performance of sulfide solid electrolyte membranes.
[0087] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
Claims
1. A fully solid-state sulfide electrolyte membrane, characterized in that, The electrolyte membrane comprises lithium salt, binder, and sulfide electrolyte particles; The adhesive is epoxy-modified nitrile rubber; the epoxy groups on the epoxy-modified nitrile rubber molecular chain can undergo a controllable ring-opening reaction with lithium salt, and anchor the lithium salt to the polymer chain through chemical bonding. The sulfide electrolyte particles include a first sulfide electrolyte particle and a second sulfide electrolyte particle, wherein the first sulfide electrolyte particle has a D50 of 3μm to 10μm and a SPAN value of ≤2.0; and the second sulfide electrolyte particle has a D50 of 0.1μm to 2.5μm and a SPAN value of ≤2.
0.
2. The electrolyte membrane according to claim 1, characterized in that, Based on the mass of the all-solid sulfide electrolyte membrane as 100%, the mass content of the lithium salt is 0.5% to 2.0%; the mass content of the binder is 1.5% to 2.0%; the mass content of the first sulfide electrolyte particles is 76% to 89%; and the mass content of the second sulfide electrolyte particles is 9% to 20%.
3. The electrolyte membrane according to claim 1 or 2, characterized in that, The mass ratio of the first sulfide electrolyte particle to the second sulfide electrolyte particle is (4-10):1; And / or, the first sulfide electrolyte particle and the second sulfide electrolyte particle are made of the same or different materials, and are each independently selected from Li6PS5Cl, Li6PS5Br, Li6PS5I, Li 5.5 PS 4.5 Cl 1.5 At least one of them; And / or, the lithium salt is selected from at least one of lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, lithium tetrafluoroborate, and lithium bis(trifluoromethylsulfonyl)imide; And / or, the preparation method of the epoxy-modified nitrile rubber includes: mixing 8g to 12g of nitrile rubber with 120mL to 150mL of non-polar solvent and stirring until completely dissolved; heating to 60℃ to 70℃; adding 8.0g to 10.0g of glacial acetic acid to the mixed solution; then adding 15.0g to 20g of a 30wt% hydrogen peroxide aqueous solution dropwise; and reacting at a constant temperature for 4h to 6h. After the reaction is completed, the reaction mixture is neutralized with a 3wt% to 5wt% sodium carbonate solution to adjust the pH value to 7-7.
5. The neutralized reaction mixture is then coagulated in anhydrous ethanol to precipitate polymer solids, which are washed 2 to 4 times. The obtained polymer solids are placed in a vacuum oven and vacuum dried at 60℃ to 70℃ for 24h to 48h until constant weight is obtained, thus obtaining the epoxy-modified nitrile rubber.
4. A method for preparing an all-solid-state sulfide electrolyte membrane according to any one of claims 1-3, characterized in that, The preparation method includes: (1) The binder and non-polar solvent are first mixed to obtain mixture a; (2) Mix the mixture a obtained in step (1) with a polar solvent and a lithium salt to obtain mixture b; (3) The sulfide electrolyte particles and the mixture b obtained in step (2) are mixed for a third time to obtain an electrolyte slurry; (4) The electrolyte slurry obtained in step (3) is coated on the substrate to obtain a wet film. The wet film is then vacuum dried to obtain the all-solid sulfide electrolyte membrane.
5. The preparation method according to claim 4, characterized in that, In step (1), the nonpolar solvent is p-xylene; And / or, the conditions for the first mixing include: a temperature of 20°C to 30°C and a time of 24h to 48h.
6. The preparation method according to claim 4 or 5, characterized in that, In step (2), the polar solvent is selected from at least one of acetonitrile, ethyl acetate, and dimethyl carbonate; And / or, the conditions for the second mixing include: a temperature of 20°C to 30°C and a time of 12h to 24h.
7. The preparation method according to claim 4 or 5, characterized in that, In step (3), the conditions for the third mixing include: a temperature of 20℃ to 30℃, a time of 30 min to 40 min, and a stirring rate of 200 rpm to 300 rpm.
8. The preparation method according to claim 4 or 5, characterized in that, In step (4), the thickness of the wet film is 40 μm to 60 μm; And / or, the vacuum drying conditions include: a temperature of 80℃~100℃ and a time of 12h~24h.
9. The preparation method according to claim 4 or 5, characterized in that, In the preparation method, the mass ratio of the nonpolar solvent to the polar solvent is (2-9):1; And / or, the mass ratio of the binder to the lithium salt is (0.5-5):1; And / or, in the electrolyte slurry, the mass ratio of binder, sulfide electrolyte particles and lithium salt is 1:(40-70):(0.1-1); And / or, in the electrolyte slurry, the total mass content of binder, sulfide electrolyte particles and lithium salt is 40% to 60%.
10. An all-solid-state battery, characterized in that, Includes the all-solid-state sulfide electrolyte membrane according to any one of claims 1-3 or the all-solid-state sulfide electrolyte membrane prepared by the preparation method according to any one of claims 4-9.
Citation Information
Patent Citations
Sulfide solid electrolyte membrane, preparation method thereof and all-solid-state lithium battery
CN121260889A
Binder for battery and application thereof
CN119709048A
Structural battery integrated composite board and forming method and application thereof
CN121331935A